Grammatical equivalence in the Arabic poets of the Daulah Umawiyyah period - Muhammad Yunus Anis (Universitas Muhammadiyah Purwokerto, 2022)
This study will examine the translation products of Arabic literary works that existed in the period of the Umawiyyah. This research generally uses two approaches, namely the literature approach and the translation science approach. Based on the translation approach, this study will measure the grammatical equivalence between Arabic and Bahasa Indonesia in the literary works of Arab poets during the Daulah Umawiyyah period. Then, this study will examine the application of translation techniques and methods in the literary works of the Arab poets of the Umawiyyah period. As for the approach to Literature, this research will investigate the product of the translation of literary works of Arab poets in the period of the Daulah Umawiyyah structurally. The diversity in Arabic Indonesian translation can be found in some aspects such as: (1) number, (2) gender, (3) person, (4) tense and aspect, and (5) voice. In addition, the application of translation techniques has a significant impact on the quality of Arabic poetry translation.